Physical and Mechanical Behaviours of Tympanotonus Fuscatus Reinforced Polyethylene - Obasa, Victoria Dumebi; Okonkwo, Samuel; Olanrewaju , Oludolapo Akanni; Adeosun, Samson Oluropo; Omotoso, Olugbemi; Omoolorun, Adebola (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
This paper investigated the physical and mechanical characteristics of the periwinkle shell (Tympanotonus fuscatus) particle to determine its effectiveness as reinforcement in polyethylene matrix composite for potential engineering applications with a reduction in fossil-based constituents with its attendant environmental impact. The composites were constituted from periwinkle particle fractions from 5 to 40 wt. %, with five different particle sizes: 106, 150, 177, 250, and 420 μm. Test specimens were investigated via Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), tensile, impact, and flexural, density, and water absorption evaluations. Results showed that densities of samples at all particle sizes increased with filler content but reduced with enlargement of the particle size of the filler owing to the increase in void sizes between the filler and the matrix. However, the developed composites still feature within the density range of low-density, to linear low-density of polymer composite. The water absorptivity decreased as the filler content increased due to the crystalline nature of the filler. Specifically, composites' peak impact energy, and flexural strength, of 21.54 J for 150 μm sample at 40 wt. % filler content and 11.96 MPa for 106 µm sample at 5 wt. % filler content was recorded respectively. FTIR spectrum shows the presence of additional C=C and C-O-C groups. Also, SEM micrographs indicated strong interfacial bonding between the filler and the matrix, and good filler dispersion in the matrix, which accounted for relative improvement in mechanical properties. Hence, the developed periwinkle particulate-reinforced low-density polyethylene composite can be used for decorative purposes or in car interior design where high strength is not a critical requirement.